Analysis of the dynamic state of the system "fixture – workpiece" - V. О. Ivanov; V. E. Karpus; І. М. Dehtiarov; І. V. Pavlenko; Y. Rong (Журнал інженерних наук)
In this article the vibrations of the “fixture – workpiece” system arising during the cutting process at various manufacturing steps under machining of levers in different fixture systems were investigated by means of numerical simulation methods. The workpieces from different materials were investigated during modeling. The results of harmonic analysis showed that the dynamic stiffness of modular adjustable fixture is higher than the stiffness of the dedicated fixture and the modular fixture. The amplitude of the vibrations in the points of machining surfaces in the modular adjustable fixture does not exceed the tolerances on the manufacturing of lever.